Can Company Value In Intervening By Profitability And Capital Structure (Manufacturing Sector Evidance Listed on IDX 2012-2017) - Fitria Haquei (Publisher Cv. Inara, 2021)
This study aims to examine the effect of profitability mediation and capital structure on the effect of company growth on firm value. The study was conducted on manufacturing companies listing on the Indonesia Stock Exchange in 2012-2017 with a total sample of 17 companies. The research data was analyzed using causal step regression analysis and product of coefficient models with the help of the SPSS version 19.00 application. The results of testing the hypothesis obtained by sales growth is not significant to the value of the company. Sales growth has a negative effect on profitability. Profitability has a significant positive effect on firm value. The company's growth has a significant positive effect on capital structure. Capital structure has a significant negative effect on firm value. Profitability does not mediate the influence of company growth on firm value. Capital structure is able to mediate the influence of company growth on firm value.